Changes in soil quality indicators in response to land use based on a minimum data set - Carlos Bravo-Medina; Danilo Sarabia-Guevara; David Sancho-Aguilera (Scientia Agropecuaria)
The Ecuadorian Amazon region is permanently subject to deforestation processes and in parallel to the implementation of agricultural, and livestock management systems that can affect soil quality. This study assessed the effect of different land use types on soil quality using the Integrated Soil Quality Index (SQI) and minimum indicators. To do this, it considers representative soil samples, 4 types of land use, and a productive landscape in the province of Pastaza. The land use types evaluated were sugarcane (SC), agrosilvopastoral System (ASPS) silvopastoral timber system (SSTT), and secondary forest (SF). Land use type had significant effects on some soil properties and, therefore, on soil quality. The soil quality index was developed using BD, Ca+Mg/K, and SOM which had the highest weighting values, suggesting a higher contribution to the final SQI. The Soil Quality Index (SQI) showed significant differences (p < 0.05) between the different land uses, establishing the following order: SSPM (0.41) > SC (0.40) > B (0.34) > SASP (0.33). Therefore, the values obtained are considered low to moderate quality with SSPM and SC as the highest quality land uses. It is concluded that soil quality can be assessed and compared more accurately in the studies of land use using the current indexing framework due to its simplicity and quantitative flexibility. However, to evaluate soil quality more comprehensively and precisely, biological properties of soils should also be considered for SQI in future studies.